ANALISA DAN DAMPAK RESIKO PENAMBANGAN EMAS ILEGAL DI KABUPATEN SIJUNJUNG - Jon Hafnil (Ensiklopedia Sosial Review, 2022)
Sijunjung location of the gold mining (illegal) From field observations found mining community provide location which is at the location of the farm like, Kabun, Stone Manjulur, Silokek, Palangki, Mundam Way, Muaro, Cape Ampalu, some mining sites along the stream Ombilin Sungai Batang, Batang Kuantan, Batang Sukam, Sinamar, Trunk Palangki and several other tributaries. The objective of this study (1) Assess the potential risks and impacts (2) Assess the potential risks and impacts of the most dominant. (3) The strategic plan megunakan minimize the risk of this research is quantitative approach method. The results of the factor analysis has been done on the risks and impact of variables, there is a reduction of variables and grouping into factors. At the risk of a reduction in the variable variable variable 4 X1.7, X1.8, X1.9 and X1.10 as communalitiesnya test value <0.5 and variables that pass the test can establish three factors, grouped into direct physical risk factors happens, risk factors of environment, risk factors of economic, social, obtained through a loading factor. Next look for the most dominant factor seen from the eigenvalues as the highest risk factor Physical immediate. While the variable impact of a reduction in the three variables: the variable X2.4, X2.6 and X2.19, because communalitiesnya test value <0.5 and variables that pass the test can form the 4 factors were grouped into Positive Economic Impact factor, factor Social impact Positive factors Negative impact of Economic and Social Negative impact factor, it is obtained through a loading factor. Next look for the most dominant factor seen from the eigenvalues as the highest impact factor Positive Economics.